Pengaruh Edukasi tentang Konsumsi Minuman Manis dan Bersoda terhadap Pengetahuan Remaja tentang Penyakit Ginjal - Irfan Sazali Nasution; Sumaya Ananda Siagian; Syalwa Madani; Noor Asninaeka Azzahra S Meliala; Lola Claudia (CV. Rayyan Dwi Bharata, 2026)
The consumption of sugary and carbonated beverages among adolescents has increased significantly and may contribute to various health problems, including kidney disorders. Limited awareness among adolescents regarding the adverse effects of excessive sugar intake is one of the factors that may increase the risk of non-communicable diseases in the future. Therefore, health education is needed to improve adolescents' knowledge and awareness of the importance of limiting the consumption of sugar-sweetened beverages. This study was conducted to determine the effect of health education on students' knowledge regarding the impact of sugary and carbonated beverage consumption on kidney health. This study employed a pre-experimental method using a one-group pretest-posttest design. This method was selected because it enables the measurement of changes in respondents' knowledge before and after the intervention in the form of health education. The study involved 22 students of SMK Gelora Jaya Nusantara Medan as respondents. Data were collected using pretest and posttest questionnaires and analyzed descriptively using frequency and percentage distributions. The results showed an improvement in respondents' knowledge after receiving health education. In the pretest, 10 respondents (45.5%) were categorized as having good knowledge, which increased to 18 respondents (81.8%) in the posttest. Meanwhile, the proportion of respondents with poor knowledge decreased from 3 respondents (13.6%) in the pretest to none in the posttest. In addition to increased knowledge, respondents also demonstrated a greater willingness to reduce the consumption of sugary and carbonated beverages as an effort to maintain kidney health. In conclusion, health education was effective in improving students' knowledge and awareness regarding the impact of sugary and carbonated beverage consumption on kidney health. Future studies are recommended to involve a larger sample size, broader study settings, and longer follow-up periods to evaluate long-term behavioral changes following health education interventions.